GENERATIVE DESIGN FOR CONCEPTUAL INSTALLATIONS - Yadav, Pooja; Gupta, Shikhar; Suri, Sahil; Jadhav, Yogesh; Srinivasan T R; Nirmalrani V (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Generative design is a huge shift in the manner of thinking out conceptual works by integrating the computer processes with the artistic instincts. The essay examines the role of computer systems in assisting artists in producing shifting, flexible, and information-driven physical experiences that exceed the common boundaries of art. Generative design involves the use of factors, chance, and rule-based reasoning, to generate forms that look like they were not written by a person. It is grounded on computer creativity and algorithmic aesthetics. Through AI and machine learning technologies as well as software applications, such as Grasshopper, Processing, and Houdini, designers have the opportunity to perform repeated research and feedback processes to simulate how things grow, move, and interact in nature. The analysis investigates how generative strategies transform the work of the designer as an entity that makes to one that maintains things running. It also puts into the limelight the interaction between human knowledge and machine intelligence. Case studies of popular generative installations demonstrate the way in which such works form interesting interactive environments that evolve according to the interaction of people with them and the information regarding the surrounding environment. Besides considering how things appear, the issues that are raised in this study include psychological and ethical questions regarding authorship, unpredictable, and the sustainability of computer art over time. The given study demonstrates that generative design can transform the process of creating future conceptual art by addressing such issues as technological restrictions, control over chance and material concerns. Generative design is perceived as a form of creation and a form of thinking of how art, technology, human experience combine to form new modes of expressing ourselves and telling stories in space.